A Multimethod Approach towards Assessing Urban Flood Patterns and Its Associated Vulnerabilities in Singapore. (16th June 2016) - Chow, Winston T. L.; Cheong, Brendan D.; Ho, Beatrice H.
Abstract : We investigated flooding patterns in the urbanised city-state of Singapore through a multimethod approach combining station precipitation data with archival newspaper and governmental records; changes in flash floods frequencies or reported impacts of floods towards Singapore society were documented. We subsequently discussed potential flooding impacts in the context of urban vulnerability, based on future urbanisation and forecasted precipitation projections for Singapore. We find that, despite effective flood management, (i) significant increases in reported flash flood frequency occurred in contemporary (post-2000) relative to preceding (1984–1999) periods, (ii) these flash floods coincide with more localised, "patchy" storm events, (iii) storms in recent years are also more intense and frequent, and (iv) floods result in low human casualties but have high economic costs via insurance damage claims. We assess that Singapore presently has low vulnerability to floods vis-à-vis other regional cities largely due to holistic flood management via consistent and successful infrastructural development, widespread flood monitoring, and effective advisory platforms. We conclude, however, that future vulnerabilities may increase from stresses arising from physical exposure to climate change and from demographic sensitivity via rapid population growth. Anticipating these changes is potentially useful in maintaining the high resilience of Singapore towards this hydrometeorological hazard.